Factors that Influence Students’ Interest in Investing during The Covid-19 Pandemic - Ali Mutasowifin (Universitas Trunojoyo Madura, 2022)
The increase in the number of investors until 2021 reached 201.5% compared to 2019. The increase was dominated by students and college students. The number of investors who increased drastically remains small, compared to the total population of Indonesian society. The subject of this study are undergraduate students at IPB University. This study aims to analyze the factors that influence the interest in investing during Covid-19 pandemic through undergraduate students at IPB University. The factors being studied were investment knowledge, investment motivation, and technological progress. The samples used in this study were 100 college students, for sampling each faculty using the Quota Sampling method. The analysis method used in this study were descriptive analysis and Structural Equation Modeling (SEM)-PLS. The result of analysis show that the investment knowledge factor did not affect significantly, while investment motivation and technological progress had a positive and significant effect on the investment interest of undergraduate students at GL University during the Covid-19 Pandemic. The results that investment knowledge does not have a significant effect on investment interest need to be considered so that it does not produce a negative impact. The research will be immensely useful to different stakeholders such as government, policymakers, financial advisors, and investors in making their strategic or operational decisions.